La pertinencia de considerar a la comunidad LGBTI como grupo de atención prioritaria - Jaramillo Estrada, Esthefany Mariel (2023)
ABSTRACT: Historically, the LGBTI community in the Ecuadorian State has been victim of various abuses to their dignity and integrity as human beings, causing constant struggles and disputes to obtain the recognition of their right of equality and non-discrimination in Ecuador's internal regulations, however, it has not been enough to fully implement and guarantee the proper exercise of their rights in the daily development of the activities they carry out in society. Therefore, this research work aims to determine the relevance of considering the LGBTI community as a group of priority attention in order to guarantee their right to formal and real equality stipulated in the Ecuadorian constitution. In the methodological field, the inductive, dogmatic, historical-logical and descriptive legal method was used due to the nature of the research, together with a qualitative, dogmatic, historical-legal and descriptive legal approach, with a non-experimental design. On the other hand, the study population was focused on the first level judges of the Riobamba canton, where the sample was based on the non-probabilistic intentional type by convenience, the technique implemented was the survey, therefore, the instrument used was the questionnaire, which established the existence of a violation of the right to formal, material and real equality of the LGBTI community, which could be counteracted with its inclusion within the groups of priority attention, based on the fact that the group has the same general characteristics as the conglomerates recognized in the Constitution of the Republic of Ecuador